Peran Moderasi Komite Manajemen Risiko dalam Hubungan Antara Kualitas Audit, Kekuatan Laba, dan Perilaku Pengambilan Risiko terhaddap Kinerja Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Muhammad Alfin Najah; Muhamad Wahyudi; Masculine Muhammad Muqorobin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of audit quality, earnings power, and risk-taking behavior on firm performance, while also testing the moderating role of the risk management committee. The research was conducted on 18 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach was employed using moderated regression analysis (MRA). The results show that only earnings power has a positive and significant effect on firm performance, whereas audit quality and risk-taking behavior have no significant effect. Additionally, the risk management committee strengthens the influence of audit quality on firm performance but does not moderate the relationship between earnings power or risk-taking behavior and performance. These findings suggest that internal oversight through the risk management committee is only effective in the context of audit but not yet optimal in managing earnings or risk-taking. This study contributes to corporate governance literature in the mining sector by emphasizing the importance of an active and strategic risk management committee.